Analysis of inequality via social stratification - Luz Judith Rodríguez Esparza; Octavio Martín Maza Díaz Cortés; Julio César Macías Ponce; Dolly Anabel Ortiz Lazcano (Entreciencias: Diálogos en la Sociedad del Conocimiento)
Purpose: To analyze the contribution that social stratification provides to inequality using the Gini index as an input.